62 Therapeutic holding – can we do better in paediatrics for our mental health and learning disability patients?. (23rd February 2023) - Wilson, Nicola; Forrester, John; Vivers, Kevin
Abstract : Background: At Great Ormond Street Hospital, we have a mission of putting the 'child first and always', this includes giving them a voice in decisions about their care. This can only be done by acknowledging their rights, liberty and ability to consent or give assent for treatment. For some children and young people (YP) holding still for a clinical procedure may be something that they need support with; or it may be that due to an altered mental state in a child or YP, clinical staff need to either utilise skills in therapeutic holding or disengagement to keep them and others safe. Methods: A pan trust teaching programme was introduced to support staff to make informed decisions that take into account the rights of our children and young people and reduce the impact of trauma as a result of procedures in our care. This included digital training via our DEN that is open to all staff and study days for those that require specialised training on holding and disengagement strategies. Results: We now have significant numbers of staff trained in Therapeutic Holding and disengagement. This means that we are able to support the planning and care of patients that would have otherwise struggled to engage with procedures and might otherwise have had a traumatic experience or their treatment cancelled. Conclusion: Our care is evolving to put children and young people's rights at the top of our agendas when planning their care. This is an example of how we can improve our practice, through a comprehensive and targeted education strategy.